2013
DOI: 10.1007/978-3-642-36827-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Histone Epigenetic Marks, and Disease

Abstract: The dietary intake of essential nutrients and bioactive food compounds is a process that occurs on a daily basis for the entire life span. Therefore, your diet has a great potential to cause changes in the epigenome. Known histone modifications include acetylation, methylation, biotinylation, poly(ADP-ribosylation), ubiquitination, and sumoylation. Some of these modifications depend directly on dietary nutrients. For other modifications, bioactive dietary compounds may alter the activities of enzymes that esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 133 publications
0
1
0
Order By: Relevance
“…It is widely recognized that nutritional factors play a role in methylation events, albeit the majority of previous studies focused on methyl donors (Zempleni et al 2012). Importantly, in a recent publication, we expanded that point of view and demonstrated that FAD-dependent demethylation events, mediated by LSD1, cause an aberrant increase in the expression of albumin in human liver cells (Liu and Zempleni 2014).…”
Section: Introductionmentioning
confidence: 69%
“…It is widely recognized that nutritional factors play a role in methylation events, albeit the majority of previous studies focused on methyl donors (Zempleni et al 2012). Importantly, in a recent publication, we expanded that point of view and demonstrated that FAD-dependent demethylation events, mediated by LSD1, cause an aberrant increase in the expression of albumin in human liver cells (Liu and Zempleni 2014).…”
Section: Introductionmentioning
confidence: 69%